DETERMINATION OF THE EFFECTIVE POROSITY OF ROCK RESERVOIRS BASED ON THE VOID SPACE STRUCTURE IN THE VISEVIAN AND TURNAISIAN FORMATIONS OF THE BEREZIVSKE FIELD OF THE DNIPRO-DONETSK DEPRESSION - YEMETS, Vladyslav; BEZRODNA, Iryna (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. Currently, it is quite important to track the patterns of the internal structure of reservoirs with their physical properties. The analysis of well-logging data in the well 203 of the Berezivske field of the Dnipro-Donetsk depression is necessary to assess the prospectivity of complexly structured reservoirs. Methods. The methodology for studying the void space structure in complexly structured reservoirs involved several stages: interpretation of well logging data; determination of parameters for the initial mathematical model of the reservoir; inversion of data from acoustic surveys into a curve of the distribution of different void formats; evaluation of reservoir rock types with determination of their effective porosity. Results. Based on the data of compressional and shear wave velocities, as well as density, three distinct rock groups were identified: compacted sandstone, calcareous sandstone and limestone. The initial approximation was obtained for each rock sample, including the set of void formats and their concentration within the reservoir layers. Direct analysis of the resulting data by the authors revealed that the most optimal void formats for the investigated intervals are: for intergranular voids – 0.07 to 0.9; for transitional voids and microcracks – 0.05 to 0.077; for microcracks – 0.007 to 0.0019; for caverns – 4 to 8. Based on the research results, it has been established that granular-cavernous porosity (39,2 %) and fracturedcavernous-granular porosity (29,5 %) are prevailing types of reservoirs.  Conclusions. The calculated values of the void formats were used for these formations to quantitatively assess effective porosity based on the obtained data and specific electrical resistivity values at different depths of investigation. The resulting approximation of α = 0.6996 was selected, which reduced the error in calculating the effective porosity of reservoir rocks. The obtained results have demonstrated that the proposed methodologies are essential for understanding and quantitatively assessing the void space structure and filtration-capacitive properties of reservoir rocks, particularly when we are facing with a limited well logging data and restrictive core sampling.
Keywords: void space structure; effective porosity; well-logging data; reservoir rocks